In situ transduction of cells in human corneal limbus using adeno-associated viruses: an ex vivo study - Son, Hyeck Soo; Jun, Albert S.; Foster, James W.; Wang, Wei; Daoud, Yassine; Auffarth, Gerd U.; Roy, Madhuparna (Scientific reports, 2022)
This study aimed to evaluate the efficacy of in situ adeno-associated virus (AAV)-mediated gene delivery into the human corneal limbal region via targeted sub-limbal injection technique. Human cadaveric corneal tissues were fixed on an artificial anterior chamber. Feasibility of sub-limbal injection technique was tested using trypan blue and black India ink. An enhanced green fluorescent protein (eGFP) encoding AAV DJ was injected into sub-limbal region. After AAV injection, corneal tissues were incubated in air-lift culture and prepared for immunohistochemical analysis. Cell survivial and expression of eGFP, stem cell markers (p63α and cytokeratin 19 (KRT19)), and differentiation marker cytokeratin 3 (KRT3) were evaluated using confocal microscopy. Both trypan blue and black India ink stained and were retained sub-limbally establishing specificity of the injection technique. Immunohistochemical analysis of corneas injected with AAV DJ-eGFP indicated that AAV-transduced cells in the limbal region co-express eGFP, p63α, and KRT19 and that these transduced cells were capable of differentiating to KRT3 postitive corneal epithelial cells. Our sub-limbal injection technique can target cells in the human limbus in a reproducible and efficient manner. Thus, we demonstrate that in situ injection of corneal limbus may provide a feasible mode of genetic therapy for corneal disorders with an epithelial etiology.
Gesehen am 14.03.2023